Cousins, siblings, or copies: the genomics of recurrent Staphylococcus aureus infections in chronic rhinosinusitis. Issue 12 (1st October 2014) - Drilling, Amanda; Coombs, Geoffrey W.; Tan, Hui‐leen; Pearson, Julie C.; Boase, Samuel; Psaltis, Alkis; Speck, Peter; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Staphylococcus aureus infection is known to play a role in recalcitrant chronic rhinosinusitis (CRS). However, it is unknown if recurrent S. aureus infections are caused by the same strain or are due to independent acquisitions of different strains. Methods Samples were collected from patients with CRS from July 2011 to August 2012. S. aureus was isolated from mucosal swabs and tissue specimens from patients who underwent surgery during the study period, or from swabs of areas of purulence taken in the postoperative period under endoscopic guidance. Pulsed‐field gel electrophoresis was used to characterize S. aureus isolates. Results Thirty‐four patients were included in the study; 79% showed persistence of the same S. aureus strain in their paranasal sinuses (p = 0.001; H1 ≠ 50%). Furthermore, a significantly high frequency of patients with known biofilm status were positive for S. aureus biofilm (p = 0.002; H1 ≠ 50%). When patients were stratified according to disease evolution postsurgery, certain strains appeared to be more commonly associated with symptom persistence. Conclusion The same S. aureus strain appears to persist in the paranasal sinuses of CRS patients despite multiple courses of culture‐directed antibiotics. This suggests that conventional antimicrobial therapies in patients with CRS may not eliminate the organism. This may be partly explained by the formation of biofilms in the paranasal sinus region.